Astrolabes for the King: The Astrolabe of Petrus Raimundi of Barcelona - Hernández, Azucena (Medieval encounters, 2017)
The astrolabe of Petrus Raimundi, made in Barcelona in 1375, occupies a significant position in the set of medieval Spanish astrolabes with Latin inscriptions, as it is the only one signed and dated that has survived to the present day. A full description and study of the astrolabe is presented in the context of the support given to the manufacturing of scientific instruments by King Peter iv of Aragon. Although the astronomical and time reckoning features of the astrolabe are fully detailed, special attention is given to its artistic and decorative features. The relationships between Petrus Raimundi’s astrolabe and those manufactured in al-Andalus, the region under Islamic rule within the Iberian Peninsula in the Middle Ages, are highlighted, as well as the links with astrolabe production in other European Christian kingdoms. The role played by astrolabes in medicine is considered and first steps are taken towards discovering the identity of Petrus Raimundi.